Phage-based biosensors for detection of microbes and biomarkers - Kulpakko, Janne (fi=Turun yliopisto|en=University of Turku|, 2022)
The detection of microbial species and communities has always been an area of great importance. Rapid methods for microbial detection are especially important in the medicine, pharmacological, and food industry. The lack of rapid and cost-effective detection methods creates a challenge to control possible epidemics. New pathogenic microbes can cause a worldwide outbreak of diseases, pandemics. The majority of currently used detection methods for pathogens have low sensitivity and specificity. Human microbiota has been demanding and mostly unexplored area before modern high-throughput methods were established. These methods have elucidated a lot of connections between different diseases and composition changes of intestinal microbiota. However, sequencing a large number of samples takes a great deal of time, work and it requires centralized facilities. For microbiota, there are no actual comprehensive and rapid sensors. Biosensors have a great potential to respond to the challenges of microbial detection. The small physical size of the equipment, ease of use and operability outside centralized hospitals are appealing characteristics of this emerging class of diagnostic devices In this thesis, the applicability of newly developed rapid biosensors were evaluated as a tool for the detection of urinary tract infection and biomarkers. The studied methods are not based on traditional immunoassay detection technology, which usually relies on detecting a single antigen from the sample. Instead, a sensitive long lifetime luminescent europium label was used with different modulating probes to nonspecifically interact with simulated samples, but also with hospital samples. Chemical probes, or phages as biological probes, were used successfully to provide multiparameter luminescence data —a fingerprint from each sample. Phage-based methods were designed to meet the challenges of rapid detection of a single bacterial species. The second phage-based study was based on lysogenic phages and tested with hospital samples the assay time was reduced. The proof-of-principle method showed sensitivity and specificity at the 90% mark when compared to the standard culture method. The method was further developed and applied to detect specific biomarkers in a controlled chemical environment and finally to classify lethal prostate cancer against non-lethal ones from urine samples. The assay demonstrated a statistically significant difference between the two groups (p<0.0014). All these results indicate that the new method has potency for a variety of screening targets or research questions.

Bakteriofageihin perustuvat biosensorit mikrobien ja biomarkkereiden havaitsemisessa Lääketieteessä, lääkeaineiden puhtaassa valmistuksessa ja elintarviketeollisuudessa mikrobien nopea havaitseminen on ensisijaisen tärkeää. Nopeille ja edullisille havaitsemismenetelmille on tarvetta varsinkin epidemioiden hallitsemisessa. Uudet patogeeniset mikrobit voivat aiheuttaa pandemioita, jotka alkuvaiheessa etenevät hyvin nopeasti maanosasta toiseen. Tämän päivän havaitsemismenetelmillä on yleisesti haasteita herkkyydessä ja spesifisyydessä. Ihmisen mikrobiota on ollut pitkään haastava ja tutkimaton alue. Tämä johtuu yksinkertaisesti siitä, ettei tähän tutkimusalueeseen ollut riittäviä tutkimusmenetemiä. Nämä nykyaikaiset menetelmät ovat selventäneet paljon yhteyksiä eri sairauksien ja suolen mikrobiotan koostumuksen muutosten välillä. Koko mikrobiotan testaukseen ei ole käytännössä todellisia pikatestijärjestelmiä. Biosensoreilla on mahdollista vastata mikrobien havaitsemisen asettamiin haasteisiin. Pieni koko, helppokäyttöisyys ja käytettävyys kenttäolosuhteissa ovat houkuttelevia tekijöitä orastavalle diagnostiikkalaitteiden luokalle. Tässä väitöskirjassa arvioitiin erilaisten nopeiden biosensorien soveltuvuutta mikrobien ja biomarkkerien havaitsemisessa. Työssä tutkitut menetelmät eivät perustuneet perinteisiin immunomääritystekniikoihin, jotka perustuvat yleensä yksittäisen antigeenin havaitsemiseen näytteestä. Tämän sijasta käytettiin näytteen kemialliselle ympäristölle herkkää europium-leimaa, jota käytettiin ei-spesifisesti vuorovaikutuksessa sekä simuloidun näytteen että potilasnäytteiden kanssa. Bakteriofagit toimivat biologisina koettimina ja tuottivat moneen eri parametriin perustuvaa luminesenssidataa -sormenjäljen jokaisesta yksittäisestä näytteestä. Bakteriofageihin perustuvat menetelmät kehitettiin ensin yksittäisten bakteerilajien havaitsemiseen ensin simuloiduissa olosuhteissa ja tämä jälkeen potilasnäytteistä. Menetelmää sovellettiin pidemmälle tunnistamaan spesifisistä biomarkkeria säädellyssä kemiallisessa ympäristössä. Lopulta menetelmää käytettiin luokittelemaan tappavat eturauhassyöpänäytteet ei-tappavista näytteistä. Luokittelutestin avulla havainnollistettiin tilastollisesti merkittävä ero näiden kahden näytetyypin välillä (p <0.0014). Yhteenvetona nämä havainnot osoittavat sen, että lantanidi-leimaan ja bakteriofaageihin perustuvaa menetelmää voidaan käyttää spesifisesti biomarkkerin, tai yksittäisen bakteerilajin havaitsemiseen